Development Of Student Entrepreneurship Skills Through The Independent Entrepreneurship Program At Gadjah Mada University 2023 - Badrul Muhayat (ASTEEC, 2024)
Entrepreneurship plays an important role in driving economic growth and creating new jobs. Therefore, the development of entrepreneurial skills among students is very important. This study aims to analyze the development of student entrepreneurship skills through the Wirausaha Merdeka program at Universitas Gadjah Mada (UGM) in 2023. The Wirausaha Merdeka program is a national program that aims to create resilient and financially independent young entrepreneurs. This research uses a qualitative approach method. Data were collected through observation and in-depth interviews with students participating in the Wirausaha Merdeka program at UGM. The results showed that this program has successfully developed various entrepreneurial skills of students, such as managerial, marketing, financial, leadership, and communication skills. Through a series of training, mentoring, and hands-on practice in building a business, students can apply the knowledge gained in real terms. The positive impact of this program can be seen from the increase in students' interest and motivation for entrepreneurship, as well as the emergence of new innovative business ideas. However, there are also challenges such as lack of initial capital and difficulties in reaching a wider market. This research contributes to providing insight into the role of the Wirausaha Merdeka program in developing students' entrepreneurial skills and provides recommendations for future program improvements.